Planning Approach for Robust Manufacturing Footprint Decisions - Philipp Sprenger; Matthias Parlings; Tobias Hegmanns (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
The manufacturing footprint strategy of European automotive companies has been determined in the preceding decades by a reduction of labour and operational costs and the development of new markets. Today, the automotive sector is characterised by growing number of logistic-related requirements like customisation, just-in-sequence supply and assembly of vendor parts (FAST 2025, 2013). This leads to the development of footprint planning as a multidimensional and complex decision problem with a significant impact on the competitiveness and finances of the business (Häntsch and Huchzermeier, 2013; Farahani et al., 2013). In response to this challenge, a literature review of footprint planning and facility selection methods and models for designing supply chain networks will be presented. The comparison of existing approaches shows the necessity of new models that allow robust and adaptable footprint decisions while especially considering project and market-related uncertainties. These uncertainties demonstrate the need to revise the footprint strategy continuously. Derived from the state-of-the-art analysis, a holistic planning work flow that supports decision makers in automotive industries from a supply chain design perspective with a special focus on the uncertainty of future business opportunities is presented. This approach integrates qualitative planning modules for knock-out-analyses and use-value-analyses and integrates quantitative modules (e.g. Monte Carlo simulation) for future project allocation. This planning procedure adopts a project-driven approach and allows for a multidimensional evaluation of different footprint scenarios, based on an uncertain future project and contract situation.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; manufacturing footprint decision; supply chain design; uncertainties; robustness